Calculation of Friction Force for Slurry Pipe Jacking considering Soil-Slurry-Pipe Interaction - Yichao Ye; Limin Peng; Weichao Yang; Yang Zou; Chengyong Cao (Advances in Civil Engineering)
This paper aims to provide a new approach to predict the friction resistance of slurry pipe jacking. Friction force usually constitutes the main component of jacking force. It can be calculated by multiplying an effective friction coefficient and the normal force acting on the external surface of the pipe. This effective friction coefficient is introduced to reflect the effect of contact state of pipe soil slurry, highly affected by the effect of lubrication and the interaction of pipe soil slurry. Firstly, by making some reasonable assumptions, the analytical formula of the effective friction coefficient is obtained, in which the critical quantity of contact (contact angle or width) is calculated by using the Persson contact model. Then, the analytical formula of normal force of circular pipeline is derived, which needs to determine the vertical soil pressure. To allow for a better prediction, three typical silo models are introduced and compared. Finally, a method for calculating the friction resistance of slurry pipe jacking is established. The main difference from the existing method is that this method takes into full consideration the influence of lubrication, soil properties (such as internal friction angle, cohesion, and void ratio), and design parameters (such as buried depth, overcut, and pipe diameter). By using reasonable silo models, the predicted results are in good agreement with the measured values collected from 10 in situ cases, which proves that the new approach can provide accuracy prediction of friction resistance for slurry pipe jacking with various soil conditions, and it may help for better future design and less construction costs.